A rare case of midgut malrotation leading to small bowel obstruction in an adult: a case report - Wang, Tian; Xu, Yichi; Xu, Jiawen; Zhen, Chunhua (Frontiers in Surgery, 2026)
IntroductionSmall bowel obstruction is a common acute abdominal condition in adults, but obstruction caused by midgut malrotation—a congenital anomaly affecting the normal rotation of the intestine during fetal development—is rare. However, among infants and children, midgut malrotation is more frequently observed.Case PresentationWe report the case of a 40-year-old male patient who presented with vomiting, accompanied by cessation of passing flatus and defecation, along with mild abdominal pain. After emergency admission and an enhanced CT scan of the abdomen, a typical mesenteric whirlpool sign was observed, with the cecum and appendix located in the left lower abdomen. The patient underwent emergency surgery and recovered well postoperatively.DiscussionMidgut malrotation may be asymptomatic in the early stages but is accompanied by an increased risk of intestinal obstruction and intestinal necrosis with an increased angle of torsion, and early surgical intervention is recommended for midgut malrotation in adults.ConclusionMidgut malrotation often leads to the development of intestinal obstruction in adults and is a rare cause. Imaging can be well defined, as well as determining the presence of critical conditions such as intestinal necrosis. Surgery is the only effective method of treatment at present, and early surgery after definitive diagnosis is very important.